Tingkat Kebugaran Jasmani dan Indeks Massa Tubuh Peserta Didik di SD Negeri Gejayan Kabupaten Sleman - Septyananda, Refri; Suripto, Agus Widodo (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the level of physical fitness and body mass index of students at SD Negeri Gejayan, Sleman Regency. The design of this study uses quantitative descriptive research with test and measurement survey methods. The method used in this study was a survey method using the TKJI and BMI test instruments consisting of a 40-meter short-distance run, a bending elbow hanging test, a sitting baring test, upright jumping, a 600-meter run, as well as height and weight measurements. Data analysis techniques using descriptive analysis of percentages using Microsoft Excel or SPSS. The results of the data analysis obtained the level of physical fitness of students in the